Sustainable development and Information Science: a perspective on information, technology and innovation (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Since 2015, the Research Group on Sustainability Management in Information Science at the Federal University of Santa Catarina has focused on the theme of sustainability and sustainable development in information science. The themes proposed by SITI are urgent and relevant, because information generates knowledge, technology solves problems and innovation improves products and processes. In this context, the Research Group on Sustainability Management in Information Science is presented as a model for promoting a sustainable and innovative approach, seeking to raise awareness and mobilize the scientific community and civil society on the importance of sustainability. In this way, the study aims to highlight the importance of access to information to achieve sustainable development, demonstrating the advocacy, scientific communication, strengthening, sedimentation and insertion actions carried out and promoted by the research group.